Evaluation of a nucleic acid amplification assay for the diagnosis of Clostridioides difficile infection. (October 2019) - Koyuncu-Ozyurt, Ozlem; Ozhak, Betil; Ogunc, Dilara; Ongut, Gozde; Gunseren, Filiz; Donmez, Levent; Colak, Dilek
Abstract: Clostridioides difficile is the leading cause of healthcare-associated diarrhea and the laboratory diagnosis of Clostridioides difficile infection (CDI) continues to be challenging. Accurate and rapid identification of C. difficile will reduce unnecessary antibiotic use and ensure contact isolation to control the spread of CDI. In this study, diagnostic performance of BD MAX Cdiff assay (Becton Dickinson, USA) was evaluated for the detection of C. difficile in 2502 fresh stool samples from hospitalized children and adult patients and the results were compared to toxigenic culture. The frequency of CDI in adults and pediatric patients were found as 3.3% and 6.2%, respectively. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of BD MAX Cdiff assay were found as; 100%, 99.7%, 93%, and 100% for all patients; 100%, 99.7%, 96.2%, and 100% for pediatric patients; and 100%, 99.6%, 90.2%, and 100% for adult patients, respectively. We concluded that BD MAX Cdiff assay with high sensitivity, specificity, and PPV is useful for the diagnosis of CDI. With a high NPV of 100%, BD MAX Cdiff assay is also suitable for the exclusion of CDI. Highlights: Clostridium difficile infections (CDI) have associated with hospitalized patients, and CDI is the leading cause of nosocomial diarrhea. Diagnostic performance of BD MAX Cdiff assay was evaluated for the detection of C. difficile in children and adult patients using 2502 fresh stool samples. The results of the tests were compared to toxigenic culture. BD MAX Cdiff with high sensitivity, specificity, and PPV, will certainly prove useful for the diagnosis of CDAD.